Ten lessons for economic policymakers - Andrew Leigh (Institute of Labor Economics (IZA), 2024)
Economists have played a powerful role in shaping modern Australia. Drawing on my experience as an academic economist and an economic policymaker, I outline ten principles to guide economists seeking to maximise their impact. These are to (1) Focus on wellbeing, not just dollars; (2) Think comparative advantage; (3) Ignore sunk costs; (4) Optimise, subject to constraints; (5) Use the best evidence; (6) Consider expected value; (7) Think in magnitudes, not just in signs; (8) Channel a libertarian; (9) Remember equity; and (10) Incentives matter.
Keywords: A11; A13; D04; E60; 330; economic policy; role of economics; relation of economics to social values